Exploring the role of 3d technology in the development of Chinese sculpture - Cui Longcheng; Musnin Bin Misdih (Human Resource Management Academic Research Society, 2025)
This study explores the role of 3D technology in the development of Chinese sculpture, aiming to evaluate how this emerging technological advancement is transforming traditional sculptural practices. As digital tools become increasingly integrated into artistic processes, 3D technology has emerged as a pivotal innovation in design, production, and preservation. This research employs a structured questionnaire to investigate the perceptions of professional sculptors, educator, and museum professional regarding the application of 3D printing, scanning, and modeling in sculptural art. Findings reveal that 3D technology enhances creative flexibility, production efficiency, and cultural preservation. However, challenges such as high costs, technical barriers, and authenticity concerns remain. The study contributes to the discourse on technological integration in the arts by offering practical insights into how 3D tools are reshaping Chinese sculpture in the contemporary era.